Upaya Peningkatan Pengetahuan Bahaya Penyakit Tidak Menular (PTM) Pada Masyarakat di Sumbawa - Rafi'ah Rafi'ah; Iga Maliga; Herni Hasifah; Asri Reni Handayani; Ana Lestari; Yulida Anggraini (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2026)
Non-Communicable Diseases (NCDs), particularly hypertension, have become a major public health problem that continues to increase in the community, including in Sumbawa Regency. Limited public knowledge regarding risk factors, dangers, and prevention of hypertension contributes to high incidence rates and complications that reduce quality of life and increase the economic burden on families. This Community Service Program (PKM) aimed to improve public knowledge and awareness of NCD risks and the importance of adopting a healthy lifestyle to prevent hypertension. The program was implemented using a door-to-door approach by visiting community members at their homes or workplaces. The activities included health education on healthy lifestyles and hypertension prevention, interactive discussions, and blood pressure screening. The participants were 20 residents of Sebewe Village who had risk factors for hypertension. Program success was measured through increased understanding and active participation. The results showed an improvement in participants’ knowledge before and after the educational sessions, and several participants were identified with stage I and stage II hypertension. This program had a positive impact by increasing community awareness to improve dietary habits, increase physical activity, and reduce smoking behavior in order to achieve more optimal and sustainable health outcomes.